Natural lactones and lactams : synthesis, occurrence and biological activity - Janecki, Tomasz (Weinheim, Germany : Wiley-VCH Verlag GmbH & Co. KGaA, 2014)
While there are numerous books on heterocycles and natural products, this text fills the need for an up-to-date summary focusing on recently developed and improved synthetic methods for the preparation of the most important classes of lactones and lactams - all in one volume. Comprehensive in its coverage, this book also provides readers with a brief description of the occurrence and biological or pharmaceutical activity of the compounds, and each chapter deals with a certain class of lactones or lactames to enable quick access to the information needed. A valuable resource for organic chemists.
Includes bibliographical references and index.
Online resource; title from PDF title page (ebrary, viewed September 19, 2013).
Keywords: Lactones; Lactams; SCIENCE -- Chemistry -- Organic; Lactams; Lactones; Electronic books; Electronic books